2008
DOI: 10.1086/591436
|View full text |Cite
|
Sign up to set email alerts
|

A Search for the Near‐Infrared Counterpart to GCRT J1745−3009

Abstract: We present an optical/near-infrared search for a counterpart to the perplexing radio transient GCRT J1745À3009, a source located $1 from the Galactic center. Motivated by some similarities to radio bursts from nearby ultracool dwarfs, and by a distance upper limit of 70 pc for the emission to not violate the 10 12 K brightness temperature limit for incoherent radiation, we searched for a nearby star at the position of GCRT J1745À3009. We found only a single marginal candidate, limiting the presence of any late… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 57 publications
2
11
0
Order By: Relevance
“…Finally, from the condition of radio luminosity not exceeding the spin-down luminosity reveals the distance of the source to be 8.5 kpc (for the same solid angle chosen by the previous authors), for high magnetic fields, which is much larger than that predicted by Zhang and Gil [34] and in accordance with the lower limit predicted by Kaplan et al [42]. For very high magnetic fields, the distance turns out to be smaller, but still at least ∼ 1.6 kpc which is larger than that predicted by Zhang and Gil [34].…”
Section: Explaining Gcrt J1745-3009supporting
confidence: 84%
See 1 more Smart Citation
“…Finally, from the condition of radio luminosity not exceeding the spin-down luminosity reveals the distance of the source to be 8.5 kpc (for the same solid angle chosen by the previous authors), for high magnetic fields, which is much larger than that predicted by Zhang and Gil [34] and in accordance with the lower limit predicted by Kaplan et al [42]. For very high magnetic fields, the distance turns out to be smaller, but still at least ∼ 1.6 kpc which is larger than that predicted by Zhang and Gil [34].…”
Section: Explaining Gcrt J1745-3009supporting
confidence: 84%
“…Zhang and Gil [34] argued it to be a WDP with a period of 77.13 minutes within 0.8 kpc. Later on, by color-magnitude analysis, Kaplan et al [42] showed that WDs with typical temperatures (5000 − 20, 000 K) and radii (5000 km) could not be this much close to us and would be at least at around 2 kpc. This challenged the idea of the source to be a WDP.…”
Section: Explaining Gcrt J1745-3009mentioning
confidence: 83%
“…Hence, an ultracool dwarf could be progenitor of the GCRT. Kaplan et al (2008) have considered the object 'C' as a possible progenitor of the GCRT. However, emission from an ultracool dwarf (L4.5V) do not produce a good fit to the observed multi-band photometry of the object C. We find the goodness of the fit do not change significantly (rms error ∼0.3 magnitude) from Kaplan et al (2008) results when the suggested K7V star is replaced by a ∼0.1 M ⊙ star ∼0.1 Gyr old (Baraffe et al 1998).…”
Section: Distance To the Gcrt And Its Classificationmentioning
confidence: 99%
“…Such a distance matches the 10 20 K cyclotron brightness temperature limit (radius ∼0.15 R ⊙ ). However, considering the uncertainty (∼0.1 magnitude) in the IR magnitudes (Kaplan et al 2008) and in the theoretical model, the quality of the fit is marginal and object 'C' is considered only as a candidate progenitor of the GCRT. We, however, note that a hithertho undetected ultracool dwarf located 200 pc (Kaplan et al 2008) could also be the progenitor of the GCRT.…”
Section: Distance To the Gcrt And Its Classificationmentioning
confidence: 99%
See 1 more Smart Citation